Lead optimization of 2-hydroxymethyl imidazoles as non-hydroxamate LpxC inhibitors: Discovery of TP0586532. (15th January 2021) - Ushiyama, Fumihito; Takashima, Hajime; Matsuda, Yohei; Ogata, Yuya; Sasamoto, Naoki; Kurimoto-Tsuruta, Risa; Ueki, Kaori; Tanaka-Yamamoto, Nozomi; Endo, Mayumi; Mima, Masashi; Fujita, Kiyoko; Takata, Iichiro; et al.
Graphical abstract: Abstract: Infectious diseases caused by resistant Gram-negative bacteria have become a serious problem, and the development of therapeutic drugs with a novel mechanism of action and that do not exhibit cross-resistance with existing drugs has been earnestly desired. UDP-3- O -acyl- N -acetylglucosamine deacetylase (LpxC) is a drug target that has been studied for a long time. However, no LpxC inhibitors are available on the market at present. In this study, we sought to create a new antibacterial agent without a hydroxamate moiety, which is a common component of the major LpxC inhibitors that have been reported to date and that may cause toxicity. As a result, a development candidate, TP0586532, was created that is effective against carbapenem-resistant Klebsiella pneumoniae and does not pose a cardiovascular risk.